Investigating of the Relationship of Psychological Factors with Immunological and Physiological Factors According to Moderator Role of Type D Personality Characteristic in Patients a waiting for Surgery in Imam Khomeini Hospital, Ilam, Iran - Ehsan Nazari; Jahansha Mohamadzadeh; Afra Khosravi; Vahid Ahmadi; Sattar Kikhawani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2020)
Introduction: Surgery is a very stressful situation for patients. In addition to physical variables, psychological components also affect the patients who are ready for surgery. This study aimed to investigate the relationship of psychological factors with immunological and physiological factors regarding the moderating role of personality trait D in patients ready for surgery at Imam Khomeini Hospital, Ilam, Iran.